2019
DOI: 10.1080/21663831.2019.1604442
|View full text |Cite
|
Sign up to set email alerts
|

Response of solidification cellular structures in additively manufactured 316 stainless steel to heavy ion irradiation: anin situstudy

Abstract: In-core or cladding structural materials exposed to heavy ion irradiation often suffer serious irradiation-induced damages. Introducing defect sinks can effectively mitigate irradiation-induced degradation in materials. Here, we investigated the radiation response of additively manufactured 316 austenitic stainless steel with high-density solidification cellular structures via in situ Kr ++ irradiation at 400°C to 5 dpa. The study shows that the cellular walls with trapped dislocations can serve as effective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The lower density in the AMT material resulted in a lower hardness and swelling after radiation, which meant that the SS 316L generated via AMT shows a better tolerance to helium radiation than the traditional material. Under heavy ion Kr ++ irradiation [63], the AMT material only showed a slight increase in dislocation loop density throughout the microstructure, but the microstructure itself remained largely unchanged. In fact, this in situ study showed that the loop density in conventional 316 SS was nearly four times as much as that in the irradiated AMT 316 SS across all dose levels (0-5 dpa).…”
Section: Radiationmentioning
confidence: 97%
See 1 more Smart Citation
“…The lower density in the AMT material resulted in a lower hardness and swelling after radiation, which meant that the SS 316L generated via AMT shows a better tolerance to helium radiation than the traditional material. Under heavy ion Kr ++ irradiation [63], the AMT material only showed a slight increase in dislocation loop density throughout the microstructure, but the microstructure itself remained largely unchanged. In fact, this in situ study showed that the loop density in conventional 316 SS was nearly four times as much as that in the irradiated AMT 316 SS across all dose levels (0-5 dpa).…”
Section: Radiationmentioning
confidence: 97%
“…Neither studies showed the generation of any secondary phases when exposed to radiation. Other in situ studies of L-PBF 316L have focused on studying the underlying mechanisms and microstructure of the material under heavy ion irradiation [63]. In all three studies, the researchers showed that microstructural features unique to AMTs such as cellular structures, sub-grain boundaries, and nano-inclusions act as defect sinks (Figure 2.7), therefore alleviating the void swelling in the material and improving its performance under irradiated environments.…”
Section: Radiationmentioning
confidence: 99%
“…As one of the most widely used materials in public hygiene areas, stainless steel (SS) has been investigated extensively because of its numerous excellent properties such as high strength, corrosion resistance, superior workability and good biocompatibility [1][2][3][4][5]. However, SS has no inherent antibacterial property [6], which may result in infection from SS implants or disease transmission via random contact with contaminated SS surfaces [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Such significant microstructure damages can cause swelling, hardening, embrittlement, and other problems in materials which significantly shorten their service life [33,34]. The irradiation stability of a material can be strengthened through introducing defect sinks, such as grain boundaries (GBs) [35][36][37][38], twin boundaries (TBs) [39][40][41][42][43][44][45], and free surface [46][47][48][49][50][51][52], which facilitate the recombination of irradiation-induced defects and defect clusters. It is well known that interfaces may also act as effective defect sinks [53].…”
Section: Introductionmentioning
confidence: 99%